Design and Performance Evaluation of a PWM-Controlled Vertical Pressure Filter for Solid–Liquid Separation of Nickel Laterite Slurry - Moh . Afandy; Isran Asnawi; Hendi Lilih Wijayanto; Eriek Aristya Perdana; Muhammad Ikbal Rianto; Fathurrasuli Fathurrasuli (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2026)
This study presents the design results of a Vertical Pressure Filter based on Pulse Width Modulation (PWM) using a linear actuator for the separation process of nickel laterite slurry. The development of this system is motivated by the limitations of conventional filtration systems that still use fixed pressure and are less flexible in regulating filtration pressure. The research method used is Design and Development (DD), which includes the design of mechanical and electronic systems, development of PWM control circuits, prototype realization, and system performance testing. Tests were carried out on variations of PWM duty cycles of 20%, 40%, 60%, 80%, and 100% to evaluate the actuator response and filtration performance. The results show that increasing the PWM duty cycle increases the actuator speed and vertical pressure in the filtration chamber. The duty cycle range of 20%–40% provides a more stable actuator response with low vibration and is suitable for the nickel laterite slurry filtration process. In addition, the system was able to produce a filtrate efficiency of 3.76% and a residue efficiency of 76.7%, which indicates the ability to form a filter cake and retain solids in the filtration media. The results of the study indicate that the PWM-based Vertical Pressure Filter has the potential as an adaptive, simple, and flexible filtration system for laboratory and pilot plant applications in nickel laterite processing.